Acute effects of loaded half-squat jumps on sprint running speed in track and field athletes and soccer players - Vanderka, M.; Krcmar, M.; Longová, K.; Walker, S. (The Journal of Strength and Conditioning Research, 2016)
The purpose of the study was to determine the acute responses to a jump squat protocol designed to induce postactivation potentiation on sprint running performance in experienced track and field athletes and soccer players. Twenty-five regional level athletes (12 track and field: ~17 years; ~177 cm; ~73 kg and 13 soccer: ~18 years; ~175 cm; ~72 kg) performed 2 test sessions assessing 40-m sprint running performance in a balanced, crossover design. Dual-beam light timing gates measured 0-20 and 20-40 m sprint times before and after either 9 minutes of sitting (control) or 2 sets of 6 repetition half-squat jump with the load eliciting maximum power (experimental) conditions. Sprint performance was significantly enhanced over both 0-20 m (3.09 ± 0.07 to 3.04 ± 0.08 seconds; d ~1.5%; p = 0.05) and 20-40 m (2.42 ± 0.09 to 2.39 ± 0.09 seconds; d ~1%; p = 0.05) in track and field athletes only. Also, the magnitude of enhanced sprint performance was related to baseline 0-20 m sprint performance (r = 0.44; p = 0.028; n = 25). It seems that using loaded half-squat jumps to enhance sprint performance could be used in training of high-level young athletes.